Virtual Instrumentation Approach for Teaching EMC Concepts - Lunca, E.; Salceanu, A. (Elektronika ir Elektrotechnika, 2012)
This paper illustrates the possibility of using virtual instrumentation techniques for enhancing the conventional EMC learning environment. After a short introduction into the EMC curricula, the main considerations for adopting a LabVIEW approach to create EMC educational tools are given. Then, a number of virtual instruments (VIs) concerning various EMC concepts, utilized during the EMC courses delivered by the authors, are briefly introduced. Three of them – a hardware-based VI module for experimenting with radiated electromagnetic interferences, an interactive simulation for teaching the radiation properties of the dipole antenna and an example of calculation program for EMC, which computes electrical parameters for typical PCB transmission lines – are presented in detail as case studies. Ill. 5, bibl. 22, tabl. 1 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.117.1.1057